2018
DOI: 10.1093/cje/bey031
|View full text |Cite
|
Sign up to set email alerts
|

An empirical contribution to Minsky’s financial fragility: evidence from non-financial sectors in Japan

Abstract: This study presents an empirical analysis to detect Minsky's financial fragility and its determinants in the nonfinancial sectors in Japan, with particular attention paid to differences between sectors and sizes. While Minsky developed theoretical analyses of financial fragility for use in economic growth models, its empirical application is limited. Based on the financial fragility indices derived from a cash flow accounting framework and Minsky's margins of safety, I detect the overall configuration and evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
19
0
8
Order By: Relevance
“…This line of research, first suggested by Nishi (2016), could be promising and should be developed in future works in this field. Nishi (2016, 36).…”
Section: Final Remarksmentioning
confidence: 97%
See 3 more Smart Citations
“…This line of research, first suggested by Nishi (2016), could be promising and should be developed in future works in this field. Nishi (2016, 36).…”
Section: Final Remarksmentioning
confidence: 97%
“…First are works that analyze the trends of aggregate variables and elaborate on how they help to explain recessions or crises, such as Estenson (1987). Second are studies that use the Minskyan hedge, speculative, and Ponzi categories and aim at detecting one or more of these categories, such as Schroeder (2009) and Nishi (2016).…”
Section: An Empirical Analysis Of Financial Fragility: a Brief Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…O nível de robustez ou de fragilidade financeira de uma economia dependeria da composição das unidades econômicas entre essas três categorias. Apesar da preocupação predominantemente macroeconômica da literatura minskyana, alguns poucos autores dessa tradição caminharam no sentido de realizar avaliações da fragilidade financeira a partir de um foco setorial (MULLIGAN, 2013;TYMOIGNE, 2014;NISHI, 2016;ROLIM et al, 2016;DAVIS et al, 2017;PEDROSA, 2017). Entretanto esses trabalhos, em geral, deram importância a segmentos que têm relevância sistêmica, a exemplo do sistema financeiro, ou avaliaram vários setores produtivos simultaneamente, como um passo preliminar para quantificar o risco financeiro da economia como um todo.…”
unclassified